PENGARUH KEJENUHAN BELAJAR TERHADAP PRESTASI BELAJAR SISWA DALAM PEMBELAJARAN MATEMATIKA - Hery Kristanto, Vigih (Widya Warta, 2017)
The purpose of this research was to find out in writing, whether the mathematics achievement of students could be improved through the implementation of the lesson plans based on the Multiple Intelligences. This type of research was the study of literature, with five stages, namely (1) collecting the literature and then reviewed some important terms in the study, (2) collecting the results of relevant literature researches, (3) conducting in-depth analysis based on all of the literatures that had been obtained by preparing the analysis, (4) developing conclusions based on the analysis, (5) making recommendations based on the obtained findings. The conclusion of this study is a written application of the lesson plan based on Multiple Intelligences has a tendency to increase student mathematics achievement.